Respuesta :

(3x - 5) - (4x + 6)
3x - 5 - 4x - 6 (Distribute the negative)
3x - 4x - 5 - 6 (Rearrange to make like terms next to one another)
-x - 11 (Combine like terms)

Answer:

The given expression (3x − 5) − (4x + 6) =  -x - 11.

Step-by-step explanation:

Given : Expression (3x − 5) − (4x + 6).

We have to simplify the given expression.

Consider the given expression (3x − 5) − (4x + 6).

Remove Parentheses , [tex]-(a)=-a[/tex]

we have,

(3x − 5) − (4x + 6) = 3x - 5 - 4x -6

Combining like terms, we have,

LIKE TERMS are terms having same variable with same degree.

here 3x and -4x are like term  and -5 and -6 are like terms,

Simplify, we have,

= 3x - 4x - 5 - 6

= -x - 11

Thus, the given expression (3x − 5) − (4x + 6) =  -x - 11.

ACCESS MORE